HR practices, organizational commitment and turnover intention: a study on employees in Klang Valley, Malaysia - Juhdi, Nurita; Pa'wan, Fatimah; Hansaram, Ram Milah@Simranpreet Kaur; Othman, Noor Akma (2011)
The study is to examine the impact of HR practices on organizational commitment and turnover intention. Four hundred and fifty seven employees from various industries in a region in one of the states in Malaysia participated in the survey. HR practices were measured using employees’ perception on career management, person-job fit, compensation and performance appraisal. All the four HR practices were found significantly related to organizational commitment and negatively related to turnover intention. Another important finding is organizational commitment was found as a partial mediator between HR practices and turnover intention. Given the findings, HR policies should be well designed because they were found to give strong effect in explaining the variance in organizational commitment.